PMMA-copolymerized color tunable and pure white-light emitting Eu3+–Tb3+ containing Ln-metallopolymers. Issue 7 (3rd February 2017) - Feng, Wei-Xu; Yin, Shao-Yun; Pan, Mei; Wang, Hai-Ping; Fan, Ya-Nan; Lü, Xing-Qiang; Su, Cheng-Yong
Abstract : Homo or hetero Ln-metallopolymers with tunable multicoloured and white light emission were fabricated by anchoring lanthanide coordination monomers onto PMMA backbone via pre-designed vinylbenzyl-substituted NTB-type ligand. Abstract : By anchoring lanthanide coordination monomers onto a PMMA polymer backbone via a pre-designed vinylbenzyl-substituted NTB-type ligand, we succeeded in the fabrication of homo or hetero Ln-metallopolymers that can emit tunable and designable multicoloured photoluminescence as well as white light emission. Copolymerization results in the fine-tuning of the energy state of the ligand in the metallopolymer compared with that in the coordination monomer, thereby changing the energy transfer efficiency to Eu 3+ and Tb 3+ centers in opposite ways. And further designing of hetero-lanthanide metallopolymers leads to additional energy transfer between Eu 3+ and Tb 3+, facilitating the generation of pure white light emission. In general, the facile and controllable synthesis procedure, versatile and reproducible combination of lanthanides, ligands and polymer backbones, and relatively high white light emitting luminous efficiency (>5%) prove this method to be promising in future lighting WPLED applications.